Sustainable urbanization: the case of Dhaka city - Hosen, Md. Khaled; Quddus, S. M. Abdul (2020)
Dhaka is one of the most populated megacities in the world. Scholars argued that, this city requires to adopt policies and strategies to achieve minimum standards of sustainable urbanization. Bangladesh has poor performance in designing a comprehensive strategic plan for the sustainability of the city. Dhaka is facing the challenges of demography, economic, and environmental adversity. Experts of urbanization are raising now the question of livability in this city. Most literature on the Dhaka city mainly focuses on the diverse problems alarming the existence of the city. Unfortunately, there is poor analysis in understanding and discovering the strategies of urbanization for Dhaka in line with the theoretical framework of sustainability. Finding possible strategies is essential for adopting policies to minimize the challenges and ensure the sustainability of the city. This study first, focuses on the theoretical analysis of urban sustainability to figure out suitable strategies for the development of the Dhaka. Secondly, it identifies five major areas and three strategic steps of sustainable urbanization. Third, it critically examines the previous initiatives taken for the urban solution of the Dhaka and their gapes in the planning and implementation process. Fourth, it investigates the challenging factors and explains what are the reasons for these factors deterring for achieving sustainability and finally, this study provides the possible solutions to existing challenges for suitable urbanization. Data for this study are collected mainly from secondary sources, such as published reports, books, peer-reviewed journal articles, newspaper reports. This study expects to contribute towards understanding the policy strategies of achieving sustainable urbanization of the Dhaka city.